Dampak Perilaku Makan Terhadap Kejadian Pre Eklamsia pada Ibu Hamil - Yetty Wilda (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2020)
Preeclampsia (PE) is a contributor to maternal and infant mortality and morbidity. Preeclampsia is the second largest cause of maternal death, affecting 3% to 8% of pregnant women worldwide. The prevalence of preeclampsia in pregnant women in Magetan Regency in 2017 is 189 people, while in 2018 there are 270 people. An increase in the incidence of preeclampsia from 2017 to 2018 is as many as 81 people. The purpose of this study was to analyze the risk of eating behavior during pregnancy to the incidence of preeclampsia at the Panekan Health Center in 2018. This study was an observational analytic study with a retrospective approach (case control). The subjects of this study were maternity mothers, 27 respondents in the case group and 27 respondents in the control group, so the total was 54 respondents. Data collection was carried out using a questionnaire, carried out on maternal in the working area of Panekan Health Center in 2018. The analysis technique used was logistic regression. The results of the study using logistic regression of eating behavior obtained p = 0.00 (p